Trends in library and information science : felicitation volume of Shri H.J. Upadhayay - Shukla, K. H. 1953-; Majmudar, K. J. (Jaipur : RBSA, 1995)
Contributed essays in honor of director of libraries in Gujarat State.
Includes bibliographical references.
Keywords: Libraries -- India; Library science -- India; Information services -- India